Local governance and public goods provision in rural China - Zhang, Xiaobo; Fan, Shenggen; Zhang, Linxiu; Huang, Jikun (International Food Policy Research Institute, 2002)
In developing countries, identifying the most effective community-level governance structure is a key issue and, increasingly, empirical evaluation of the effects of democratization on the provision of local public goods is needed. Since the early 1990s, tens of thousands of villages in rural China have held local-government elections, providing a good opportunity to investigate the effect of democratization on the level of public goods provision. Using a recent village survey conducted over a significant period of time, this paper compares governance by elected officials with that of appointed cadres and finds that elected officials tend to tax constituents less and provide them with higher levels of public service. -- Authors' Abstract."